A193 GLUTEN-FREE DIET IMPROVES DYSPEPSIA-LIKE SYMPTOMS IN A PILOT STUDY OF PATIENTS WITH TYPE 1 DIABETES MELLITUS. (26th February 2020) - Miranda, P M; Rueda, G H; Calo, N; Seiler, C; Punthakee, Z; Pinto-Sanchez, M I; Bercik, P
Abstract: Background: Patients with type 1 Diabetes Mellitus (T1DM) often suffer with gastrointestinal (GI) symptoms, such as abdominal pain, bloating, early satiety, nausea and vomiting. T1DM patients are at a higher risk to develop celiac disease, and those patient with both disorders benefit from a gluten-free diet (GFD). However, it is unknown whether GFD has any benefit in patients with T1DM without celiac disease who present with upper GI symptoms. Aims: To investigate the role of GFD in the management of moderate to severe dyspeptic symptoms in non-celiac patients with T1DM. Methods: We enrolled adult T1DM patients, in whom celiac disease was ruled out by serology and/or endoscopy, suffering with two or more of upper GI symptoms. The patients were instructed to undergo a strict GFD for a period of 1 month, under supervision of a dietitian. Glycemic levels were monitored by a continuous glucose monitoring device (CGM) for 2 weeks before, and for 2 weeks at the end of the GFD period. Upper GI symptoms, general quality of life, anxiety and depression were assessed using standardized questionnaires. Blood samples were collected to assess glycaemia (Hb1Ac) and lipid profiles. Scintigraphy and videofluoroscopy were used to assess gastric emptying. Results: Seven patients finished the study so far. They reported a significant improvement in nausea (p<0.05), sensation of fullness (p<0.01), bloating (p<0.01), feeling of excessive fullness after meals (p<0.01) and having stomach visibly larger after meals (p<0.01). 5 out of the 7 patients reported an improvement in general quality of life, based on PAGI-QOL (Patient Assessment of Upper Gastrointestinal Disorders – Quality of Life), and decreased anxiety levels (HADS, Hospital Anxiety and Depression Score). There was no significant change in mean glucose level, time in target, glucose variance and HbA1c levels after GFD. However, there was a trend for less time spent in hypoglycemia, namely in those patients who experienced frequent hypoglycemia prior to GFD. Overall, there was no change in serum lipid profile or gastric emptying. Conclusions: One month of GFD improved dyspepsia-like symptoms, general quality of life and anxiety levels in T1D patients without concomitant celiac disease. GFD also improved the blood glucose management of patients with frequent hypoglycemia. Thus, this dietary intervention appears to improve upper GI symptoms in T1D patients but the results need to be replicated in a larger patient cohort. Funding Agencies: CIHR